G. W. F. Hegel on the education and upbringing of youth: speech in honor of the end of the academic year on 1811 September 2 - Grinevich, Egor A.; Vereshchako, Alexey I.; Strelkovskaya, Karina V.; Pavlenok, Diana I. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
Philosophical heritage of G. W. F. Hegel is rightfully considered the apogee of German classical philosophy. The reader is invited to look at the figure of G. W. F. Hegel from the point of view of the practice of education in this article. Texts related to the field of education have not been fully translated to Russian, which makes it difficult to form a complete picture of ideas about G. W. F. Hegel’s philosophy of education for the domestic reader. These materials contain the translation of G. W. F. Hegel’s speeches delivered as director of the gymnasium in Nuremberg in 1811, which had not been previously translated or translated fragmentarily.
Keywords: G. W. F. Hegel; the speeches by the gymnasium’s principle; G. W. F. Hegel’s pedagogical views; philosophy of education; German classical philosophy; idealism